FAKTOR-FAKTOR PENYEBAB KECEMASAN SISWA DALAM MENGHADAPI UJIAN NASIONAL - Solehah, Laila Fida Nabihah (Perspektif Ilmu Pendidikan, 2012)
National Examination implemented in primary and secondary education still becomes a contraversial issue causing negative psychological effect as anxiety for the students. Considering the factors raising the anxiety are necessary to be identified, this research is to find out and describe the factors and propose the alternatives to minimize them. Taking a palce at SMA N 19 in Jakarta in the academic year of 2010/ 2011, the research distributed questionair to the students of the 12th grade. The collected data were analysed on the basis of percentage. The factors of students’ anxiety identified in the research are (a) passing grade norms, (b) negative thinking to pass the passing grade, (c) possibility of failure, and (d) consequences of failure. As the factors of the anxiety can negatively affect the students and lower the graduate level, the research suggests the schools to handle the problem through the councillors